Matthew Ngui: public artist - Snell, Ted (Artlink Australia, 2007)
Matthew Ngui is a Singaporean born, Australian artist who makes intriguing and engaging public artworks that embrace the history of a given site. Ngui is fascinated by the ways in which we interact with artworks and the individual nuances and understandings each person brings to the encounter. Ngui describes his work as 'often loose, and multifarious, sometimes tenuous and always fragile'. Scale and ambition are other easily identifiable elements in Ngui's practice, whether it be transforming a cityscape with lights or covering a Swiss Village in an avalanche of 350,000 bouncing balls, each emitting a light and a whispered message.